Creep-resistant behavior of beta-polypropylene with different crystalline morphologies. Issue 37 (29th March 2016) - Jia, Chenfei; Liao, Xia; Zhu, Jingjun; An, Zhu; Zhang, Qiongwen; Yang, Qi; Li, Guangxian
Abstract : This manuscript investigates the creep performance of β-iPP with different crystalline morphologies. Abstract : β-Phase isotactic polypropylene (β-iPP) specimens with different contents of β-phase nucleating agent were employed to investigate the deformation-induced microstructure evolution during creep behavior. Morphological investigations by SEM showed that the crystalline morphologies of β-iPP were controlled by the content of the β-phase nucleating agent, namely, well-developed β-spherulites induced by low content of β-phase nucleating agent, bundle-like morphology with imperfect spherulites induced by medium content of β-phase nucleating agent and needle-like morphology induced by high content of β-phase nucleating agent. It was interesting to observe that all samples with different contents of β-phase nucleating agent showed a similar β/α transformation process. However, well-developed β-spherulites, which have integrated crystalline structure, showed poor creep resistance compared with the crystalline morphology nucleated by higher contents of β-phase nucleating agent. For bundle-like morphology, the crystalline phase was imperfect and obtained larger long spacing, resulting in better creep resistance. With respect to needle-like morphology, the crystalline phase was disordered and displayed largest long spacing, resulting in best creep resistance. The results of this work revealed that the creep resistance would be different with different crystalline morphologies. On the other hand, this work provided the evolution of microstructure during deformation to further explain the molecular mechanism of fatigue failure for creep.